Gambaran seroepidemiologi dan histopatologi infeksi virus parainfluenza tipe 3 pada sapi - Sendow, Indrawati; Syafriati, Tatty; Damayanti, Rini (Indonesian Animal Sciences Society, 2004)
A study to gain seroepidemiological feature and histopathological changes in order to obtain a viral causative agent had been conducted against parainfluenza virus type 3 (PI-3) in infection cattle in Indonesia. Serological survey was conducted in different areas in Indonesia and from serum Bank to gain the information on the distribution of parainfluenza type 3 (PI-3) in large ruminants. A total of 1334 sera had been tested using serum neutralization test, and the result indicated that prevalence of reactors was varied from 0 to 60 %. The highest prevalence was 60% in sera detected from Bogor abbatoir. Reactors were also found in other areas such as West Java, Central Java, East Java, NTT and Papua. Titration results indicated that the distribution of titre was varied from 4 to 256, and titre of 8 to 32 was the most common. Titre of 128 and 256 was only found in each of 1 sera only. Isolation results indicated that no isolate was obtained from 237 samples processed. Histological examination showed that more than 60% had interstitial pneumonia, which indicated vairal infection had been occurred. This serological result indicated that PI-3 infection was detected in Indonesian large ruminants. Â Key words: Parainfluenza type 3 virus, serology, histopathology